Operations Rescheduling Strategies, Policies, and Methods: A Philosophic Approach - داود غسان قاسم; حمود مها عبد الكريم (Journal of Economics and Administrative Sciences, 2016)
When scheduling rules become incapable to tackle the presence of a variety of unexpected disruptions frequently occurred in manufacturing systems, it is necessary to develop a reactive schedule which can absorb the effects of such disruptions. Such responding requires efficient strategies, policies, and methods to controlling production & maintaining high shop performance. This can be achieved through rescheduling task which defined as an essential operating function to efficiently tackle and response to uncertainties and unexpected events. The framework proposed in this study consists of rescheduling approaches, strategies, policies, and techniques, which represents a guideline for most manufacturing companies operating in such dynamic changing environments, facing a wide variety of unexpected events and disruptions. Rescheduling strategies are dynamic scheduling & predictive eactive scheduling. In practice, rescheduling done either periodically or occasionally, and in some cases it done in a hybrid manner as policies to plan activities for next time periods and at the same time to response to significant disruption. Some rescheduling methods used to create robust schedules by regenerating or updating schedules. These methods are: Time Shift Rescheduling, Partial Rescheduling, and Total Rescheduling.